Insulation materials in shipboard electrical equipment: A systematic literature review on thermal classes, temperature limits, aging mechanisms, and service life prediction for maintenance planning - Syairi Anwar; Hendi Prasetyo; Febria Surjaman (Journal Marine Inside, 2026)
The reliability of shipboard electrical systems depends critically on the performance of insulation materials used across generators, motors, transformers, and power distribution networks. Insulation degradation remains a primary catalyst for electrical failures, unplanned shutdowns, and fire hazards onboard ships. This degradation is significantly accelerated by the harsh marine environment, which subjects equipment to high humidity, salt contamination, severe vibration, and continuous thermal cycling. To address these challenges, this study conducts a Systematic Literature Review (SLR) synthesizing previous research on marine electrical insulation, with a specific focus on thermal classifications, degradation mechanisms, service life estimation, and maintenance strategies. Guided by the PRISMA framework, 68 peer-reviewed publications and international standards (e.g., IEC and IEEE) published between 2000 and 2025 were systematically analyzed. The findings reveal that thermal Classes F and H currently dominate modern marine applications due to their exceptional thermal endurance. Thermal aging emerges as the most critical degradation factor; in accordance with the Arrhenius principle, operating just 10°C above the design limit can reduce insulation service life by approximately 50%. Consequently, modern condition-monitoring techniques—such as partial discharge monitoring and polarization index measurement—are increasingly vital for transitioning toward predictive maintenance. Ultimately, this review provides a comprehensive framework for optimizing insulation management and maintenance planning in maritime operations.   Keandalan sistem kelistrikan kapal sangat bergantung pada kinerja material isolasi yang digunakan pada generator, motor, transformator, dan jaringan distribusi daya. Degradasi isolasi tetap menjadi pemicu utama kegagalan kelistrikan, penghentian operasional yang tidak terencana (unplanned shutdowns), dan bahaya kebakaran di atas kapal. Proses degradasi ini dipercepat secara signifikan oleh lingkungan laut yang ekstrem, yang memaparkan peralatan pada kelembapan tinggi, kontaminasi garam, getaran keras, dan siklus termal yang terus-menerus. Untuk mengatasi berbagai tantangan ini, penelitian ini melakukan Systematic Literature Review (SLR) yang menyintesis penelitian-penelitian terdahulu mengenai isolasi kelistrikan laut, dengan fokus spesifik pada klasifikasi termal, mekanisme degradasi, estimasi usia pakai, dan strategi perawatan. Berpedoman pada kerangka kerja PRISMA, sebanyak 68 publikasi ilmiah dan standar internasional (seperti IEC dan IEEE) yang diterbitkan antara tahun 2000 hingga 2025 telah dianalisis secara sistematis. Temuan penelitian menunjukkan bahwa Kelas termal F dan H saat ini mendominasi aplikasi kelistrikan laut modern karena ketahanan termalnya yang sangat baik. Penuaan termal (thermal aging) muncul sebagai faktor degradasi paling kritis; sesuai dengan prinsip Arrhenius, pengoperasian hanya 10°C di atas batas desain dapat mengurangi usia pakai isolasi hingga sekitar 50%. Oleh karena itu, teknik pemantauan kondisi modern—seperti pemantauan peluahan sebagian (partial discharge) dan pengukuran indeks polarisasi—menjadi semakin vital untuk transisi menuju perawatan prediktif. Pada akhirnya, ulasan ini menyediakan kerangka kerja yang komprehensif untuk mengoptimalkan manajemen isolasi dan perencanaan perawatan dalam operasional maritim.